Ones and zeros : understanding Boolean algebra, digital circuits, and the logic of sets - Gregg, John; John Wiley & Sons; IEEE Xplore (Online service) (IEEE Press understanding science & technology series, 1998)
"Ones and Zeros explains, in lay terms, Boolean algebra, the suprisingly simple system of mathematical logic used in digital computer circuitry. Ones and Zeros follows the development of this logic system from its origins in Victorian England to its rediscovery in this century as the foundation of all modern computing machinery. Readers will learn about the interesting history of the development of symbolic logic in particular, and the often misunderstood process of mathematical invention and scientific discovery, in general. Ones and Zeros also features practical exercises with answers, real-world examples of digital circuit design, and a reading list." "Ones and Zeros will be of particular interest to software engineers who want to gain a comprehensive understanding of computer hardware." "Outstanding features include: a history of mathematical logic, an explanation of the logic of digital circuits, and hands-on exercises and examples."--BOOK JACKET.
Keywords: Electronic digital computers : Circuits : Design; Logic, Symbolic and mathematical; Algebra, Boolean; Set theory; Álgebras de boole; Boole, Algèbre de; Informatique : Mathématiques; Logique symbolique et mathématique; Ensembles, Théorie des